(untitled) (Medical Forum Monthly, 2021)
Objective: To evaluate the knowledge and compliance of paramedics regarding preventive measures in Sindh. Study Design: Cross Sectional Study Place and Duration of Study: This study was conducted at the Naz Memorial Hospital, Karachi from January 2020 to May 2020. Materials and Methods: 100 numbers of paramedics from different medical institutes through snow ball sampling selected. The valid questionnaire was filled by the paramedics and received via email with the ethical approval from concerned ethical bodies. Both gender with 18 years and above age were included, no medical professional other than paramedics were included in present study. Both questionnaires were filled by the participant, who voluntarily participates in the study. The data was expressed in the form of frequency and percentage through SPSS version 21.0 Results: 100% of paramedic’s well response the knowledge at higher level of appreciation regarding preventive measures and their application at their work places. They are well trained and excellent skills in their field of health care, the deficit area if the availability of resources for both the workers and patients. Conclusion: In fighting a battle against the corona virus team of paramedics are generally highly equipped with knowledge, skills and attitude. The only barriers at their work place are the availability of recourses that can make hazards in management of illness and meanwhile cure the patients and self-protection are at high risk. If the ministry involved and make sure the proper accessibility of all protective maneuvers at the site of health management, the outcomes will be more than the thought.